2015
DOI: 10.1038/srep07995
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Potent Tyrosinase Inhibitor, T1, with Significant Anti-Melanogenesis Ability by zebrafish in vivo Assay and Computational Molecular Modeling

Abstract: Tyrosinase is involved in melanin biosynthesis and the abnormal accumulation of melanin pigments leading to hyperpigmentation disorders that can be treated with depigmenting agents. A natural product T1, bis(4-hydroxybenzyl)sulfide, isolated from the Chinese herbal plant, Gastrodia elata, is a strong competitive inhibitor against mushroom tyrosinase (IC50 = 0.53 μM, Ki = 58 ± 6 nM), outperforms than kojic acid. The cell viability and melanin quantification assay demonstrate that 50 μM of T1 apparently attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 70 publications
(75 reference statements)
4
108
0
Order By: Relevance
“…Skin irritancy testing is usually performed on human keratinocytes [186]; human repeat insult patch testing (HRIPT, repeated applications of products on the skin, under an occlusive patch, in healthy adult volunteers) has also been developed to assess the dermal irritation or sensitization potency of a molecule. In vivo toxicity assays can be performed in zebrafish or mice [187].…”
Section: Further Development Of a Cosmetic Ingredientmentioning
confidence: 99%
“…Skin irritancy testing is usually performed on human keratinocytes [186]; human repeat insult patch testing (HRIPT, repeated applications of products on the skin, under an occlusive patch, in healthy adult volunteers) has also been developed to assess the dermal irritation or sensitization potency of a molecule. In vivo toxicity assays can be performed in zebrafish or mice [187].…”
Section: Further Development Of a Cosmetic Ingredientmentioning
confidence: 99%
“…9 All dienols ( 4a–4e ) possessed IC 50 values at µM levels (Table 2). Additionally, aliphatic linked dienols ( 4a–4d ) had IC 50 values statistically lower than KA itself.…”
Section: Resultsmentioning
confidence: 99%
“…9 Mushroom tyrosinase inhibition was determined by adding dienols in sample media (25 µL) to 96-well plates containing phosphate buffer (80 µL, pH = 6.8) and 125 µL substrate (0.5 mM L-DOPA) and incubated for 5 min at room temperature. 9 Mushroom tyrosinase (20 µL, 1250 U/mL, Sigma, Milwaukee, WI) in phosphate buffer (pH = 6.8) was added and incubated an additional 5 min at room temperature. The amount of dopachrome produced was measured using a microplate reader (Coulter, Boulevard Brea, CA) at 475 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al [2] also screened 78 medicinal herbal plants and found out that the rhizome of GEB has a potential to inhibit tyrosinase activity. Although GEB has been used as an oriental medicinal remedy to treat neurodegenerative disorders, there is high possibility to use GEB as a tyrosinase inhibitor from these screening studies.…”
Section: Discussionmentioning
confidence: 99%